Uma nova proposta para bloqueio da proteção de distância em linhas de transmissão durante oscilação de potência - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The Electric Power System (SEP) increases its complexity and may suffer from disturbances in the network, which can result in voltage and frequency variations that violate its operating restrictions. Among these violations, disturbances such as, for example, those caused by the disconnection of generators, which can be controlled to the point where the system reaches a new acceptable operating point, are said to be stable power swing (SPS). Thus, there is a need to combine characteristics of operation of protection relays, aiming at the rapid elimination of faults, besides guaranteeing the selectivity in the performance of these devices in regard to improper operation during the OEPs. Therefore, the use of a distance relay (ANSI function 21) is indispensable, whose performance is determined by the impedance seen by the relay, combined with an operational logic that blocks its operation during a stable power swing (ANSI function 68) , it being known that a power swing can occur constantly in an electrical system. When an oscillation of this type occurs, the apparent impedance seen by a distance relay during this phenomenon acquires oscillatory character. During such an oscillation, this variation in impedance often causes it to migrate into the operating region of the relay in the R-X plane, causing undue actuations in line protection. In order to prevent undue relaying of the distance relay, the technique proposed in this work is based on the analysis of the behavior of the samples of the network voltage signals, arranged as pairs ordered in a cartesian plane together with the respective value of the first function- difference of said signal, so that the protection acts only for short-circuit conditions and remains inoperative in cases of power oscillation. In the study, such simulations were performed in a test system implemented in the software where different stable oscillation situations were simulated for different oscillation frequencies, as well as cases of three-phase short-circuits, both with different loads and different incidence oscillation. It is also emphasized that the technique implemented in Matlab acts correctly, blocking the relay for SPS situations.
Keywords: Engenharia elétrica; Detecção; Linhas de transmissão; Sistema elétrico de potência; Relés de proteção; Curtos-Circuitos; Electrical engineering; Detection; Transmission lines; Electric power system; Protection relays; Short-Circuits; CNPQ::ENGENHARIAS